2012
DOI: 10.1002/alr.21042
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis symptoms and computed tomography staging: improved correlation by incorporating radiographic density

Abstract: Incorporation of radiographic characteristics of sinus opacification with Lund-Mackay scores offers greater predictive power of patients' subjective symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…The significant correlation between patient symptoms and the MLM score makes MLM one of only a few scoring systems that has demonstrated such a relationship [15, 16, 27]. The MLM system benefits from its objective nature and continuous scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant correlation between patient symptoms and the MLM score makes MLM one of only a few scoring systems that has demonstrated such a relationship [15, 16, 27]. The MLM system benefits from its objective nature and continuous scale.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has investigated the relationship among mucosal thickening on imaging, endoscopy findings on physical exam, and symptom severity in patients with severe CRS [15, 16, 27] and has focused on improving correlation between CT findings and symptom scores for patients with a narrow spectrum of severe disease defined by strict criteria. In contrast, the patients included in the present study were not confined to those with CRS and had relatively low burden of sinus inflammation (mean LM score of 3.9 relative to previous studies with an average LM score of 4.3 in patients without CRS and 9.8 in patients with CRS [28, 29]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have tried to identify predictive data from CT scans, and have noted that presence of osteoneogenesis on CT is associated with diminished QoL gains after surgery, 78 and also that intrasinus quantity and density of opacification may correlate with QoL measures. 79 Although both endoscopic and radiographic measures may be further refined in the future to better correlate with QoL measures and outcomes, it seems clear that they are not measuring exactly the same constructs, and failure to identify a high level of correlation with symptoms does not imply that the measure is not useful. Future research might identify other factors that predict outcome, such as measures of immune response and regulation and the status of the microbiome.…”
Section: Ivc Measurement Of Disease Severitymentioning
confidence: 99%
“…7 Sedaghat and Bhattacharyya incorporated Hounsfield units into LM scores in an attempt to better utilize density information from the CT images. 8 Both studies found that image scores better correlated with some (but not all) of the symptoms, suggesting the superiority of the objective software-based systems to subjective, visual scoring systems.…”
Section: Introductionmentioning
confidence: 99%